Rethinking the roles of pastoralists’ indigenous religious practices in Nuer nation Zone, Gambella Region, South-West Ethiopia - Chayot Gatdet (Cogent Arts & Humanities)
Indigenous religions play a crucial role in shaping the lives of pastoralist communities in the Gambella Region. However, there is a lack of focused studies on the specific roles these religions play among the Nuer pastoralists. Thus, this study aims to explore the roles of indigenous religions among the Nuer pastoralists in the Gambella Region. This study employed a mixed research design. This study used the multistage sampling technique to choose the study areas and participants. Data were collected using an interview schedule and focus group discussions from 156 respondents. The result found that appeasing spirits (82%), sacrifice (89%), divination (76%), and communal ceremonies (94%) were practiced in the study areas. These systems have highly contributed to personal reproduction (55%), farming practices (45%), conflict resolution (60%), forecasting event (48%), healing (60%), and social cohesion (70%), and local governing (50%) among the pastoralists. These indigenous religion systems faced increasing severe exposure to missionary activities (42%), modernization (35), political marginalization (30), and socio-political instability (28) that disrupts traditional governance structures. Thus, the indigenous religion systems serve for both spiritual frameworks and managing socio-economic benefits. Therefore, the concerned organizations should preserve the practices of indigenous religion systems, thereby strengthening the practical interventions.